2010
DOI: 10.1590/s0103-84782010005000072
|View full text |Cite
|
Sign up to set email alerts
|

Principais aspectos da infecção por Leptospira sp em ovinos

Abstract: RESUMO Este trabalho tem como objetivo revisar as infecções por Leptospira sp em ovinos. São abordados os aspectos epidemiológicos, incluindo a ocorrência no Brasil e as formas de transmissão, os sinais clínicos e as lesões, o diagnóstico e as medidas de prevenção e controle.Palavras-chave: leptospirose, ovelha, zoonose. Brazil and mechanisms of transmission, clinical signs and lesions, diagnosis, prevention and control measures. ABSTRACT An updated review of Leptopspira sp infection in sheep is presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 24 publications
0
8
0
12
Order By: Relevance
“…On the other hand, surveys have shown that the infection of sheep by Leptospira sp seems to be common and, in most cases, is associated with the presence of the serovar Hardjo (MELO et al, 2010), which is the one the most responsible for reproductive losses in cattle and also causes the largest number of spontaneous abortions in sheep (HERRMANN et al, 2004).…”
Section: Contentmentioning
confidence: 99%
“…On the other hand, surveys have shown that the infection of sheep by Leptospira sp seems to be common and, in most cases, is associated with the presence of the serovar Hardjo (MELO et al, 2010), which is the one the most responsible for reproductive losses in cattle and also causes the largest number of spontaneous abortions in sheep (HERRMANN et al, 2004).…”
Section: Contentmentioning
confidence: 99%
“…in sheep was first reported by Santa Rosa and Pestana de Castro (10), with a prevalence of 34% (dilution of 1:200 to 1:600) for prevalent Canicola and Icterohaemorrhagie serovars (11). The serum samples were also reactive against the serovars Pomona, Sejroe, Grippotyphosa, Batavie, Hyos and Australis.…”
Section: Historymentioning
confidence: 59%
“…The serum samples were also reactive against the serovars Pomona, Sejroe, Grippotyphosa, Batavie, Hyos and Australis. According to their results, dogs and rats served as the source of infection (11).…”
Section: Historymentioning
confidence: 99%
“…Essa eliminação pode constituir um problema zoonótico para todos que entrarem em contato com o animal 16,17,18 . A leptospirose é um problema ocupacional, pois pesquisas de isolamentos que foram conduzidas em diversos países têm demonstrado a importância dos ovinos na epidemiologia da doença, principalmente em relação à saúde pública 7,16 .…”
Section: Discussionunclassified